Notable New Yorkers of Manhattan's Upper West Side : Bloomingdale-Morningside Heights - Mackin, Jim (Book collections on Project MUSE., 2020)
Nearly 600 captivating stores of notable, former residents of Manhattan's Upper West Side, some famous, some forgotten.